Peruvian health and gastronomy under a social, economic and competitive perspective - Mauro Martin, Ismael San (2019)
Objective: In Peru, health and food sectors are related economically and socially. We aimed to demonstrate which are the opportunities and challenges of Peruvians food sector in relation to human healthcare sector, from where future decisions may be taken; and promote Technology and Technological Innovation with scientific rigor in that sector. Method: Recognize and analyze holistically the health and food sectors. Results: Their relationship has been demonstrated, as well as gaps in competitiveness and Science, Technology and Technological Innovation have been identified. Conclusion: Innovation in the field of Peruvian food sector, with a scientific rigor on behalf of population health is needed. We propose the implementation of a Science, Technology and Technological Innovation platform with the aim of standardizing the quality of traditional cuisine and developing gastronomy in Peru.